If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -3b = -5b + 2b + 18 + -3 Reorder the terms: 15 + -3b = 18 + -3 + -5b + 2b Combine like terms: 18 + -3 = 15 15 + -3b = 15 + -5b + 2b Combine like terms: -5b + 2b = -3b 15 + -3b = 15 + -3b Add '-15' to each side of the equation. 15 + -15 + -3b = 15 + -15 + -3b Combine like terms: 15 + -15 = 0 0 + -3b = 15 + -15 + -3b -3b = 15 + -15 + -3b Combine like terms: 15 + -15 = 0 -3b = 0 + -3b -3b = -3b Add '3b' to each side of the equation. -3b + 3b = -3b + 3b Combine like terms: -3b + 3b = 0 0 = -3b + 3b Combine like terms: -3b + 3b = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| -3n-8=-26 | | 15=h-17 | | 11-2(x)=-17 | | -6(w+6)=1 | | y=-4/3(1.3333)-8 | | 2x+1-5=7-1 | | 11-2x=-17 | | 4x+2=53 | | 7=8(1+2r)-5(1+3r) | | -3(4-3n)=-66 | | x+y+xy=120 | | 4/x+1/9= | | 5=5m-6 | | 2/5h-7=12/5h-2h+4 | | 5=5m+6 | | -63=5+4(1-3x) | | -6xy-2xz-9x+1=4y+4 | | x(2)+5x+6= | | 15-3b=5b+2b+18-3 | | -72=-9(m+12) | | -14=6x+34 | | (t+20)=(t-10)+t | | 3g-2g= | | 1x+10=6 | | 6x=12+3y | | -5x=14-x-2 | | 8(2-t)=-4t | | (2x+5)(3x-7)= | | x+26(2)=264 | | 8+8x=80 | | 8+-29=-24+3t | | 4(k+5)=2k+10 |